CYSTIC ADVENTITIAL DISEASE OF THE POPLITEAL ARTERY PRESENTING AS ACUTE LIMB ISCHEMIA : POPLITEAL ARTERY’S CAD PRESENTING AS ALI - Rego, Duarte (2017)
Introduction: Cystic adventitial disease is a rare cause of intermittent claudication. Its presentation as acute limb ischemia is exceedingly rare. This disease is caused by the growth of multiple cysts within the adventitia. Although its etiopathogeny isn’t fully understood most evidence supports an embryonic defect during the development of non-axial arteries. Treatment includes several options: adventitial layer excision, percutaneous aspiration of the cysts and segmental arterectomy with bypass. Methods: We present a case of acute limb ischemia caused by popliteal cystic adventitial disease. Clinical Case: A 60 years old male presented with acute limb ischemia of the right leg. Duplex ultrasound showed a tight stenosis of the popliteal artery caused by adventitial cysts. The patient was intervened: from a posterior approach an excision of the cysts and adventitial layer was performed with total recovery of foot’s perfusion and pedal pulse. After 18 months of follow-up the patient is asymptomatic without imagiological evidence of recurrence. Conclusions: Due to the disease’s rarity there are no studies designed to compare the different treatment strategies for this pathology. However, the available data from case series shows that the surgical technique chosen for this patient presents very good results and, therefore, it seems to be a good therapeutic option assuming a patent popliteal artery without intimal lesion. Clinical presentation as acute limb ischemia isn’t described in the literature and isn’t today understandable because the factors affecting mucin secretion rate by cyst’s mesenchymal cells are unknown.